Implementation Of Hope Tree Media as an Effort to Increase Learning Motivation in Al Falah Mts Students in Cibalanarik Village During the Covid-19 Pandemic - Pamungkas, Widi; Pania, Ita; Nur, Iis Balqis; Maulida, Sania; Fauzi, Vega Nurul; Hopipah, Sinta; Zalfa Alya, Lizza; Jati, Azis Fajar; Firdausi, Hilda Aliftia; Anisa, Nuraini; Khoeriyah, Sely Mawadatul; Jujun R, M. Ilham; Solihatin, Yuyun (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The wishing tree is an artificial tree that is pasted with colored paper that reads ideals. The goal is to foster a sense of optimism in students or students in achieving these goals. In addition, it can also develop and improve the creativity of teachers and students. When all the students have attached it and it resembles a tree, it becomes a wishing tree that always reminds them of their dreams. Besides that, the enthusiasm of the students at MTS Al-Falah class VII A is also very good. They are very happy to write down their hopes or aspirations in the future, what they want and how to do and also because most of them live in Islamic boarding schools they will also make it dikobong to always remember their hopes and dreams. -their goals they want to achieve in the way they prepare.